Legal Enforcement Of Innocent Passage Implementation In Indonesian Waters - Eka Widi Astuti; Oki Kustiwa; M. Arief Syahroni; Wahyu Subagyo (Fakultas Hukum Universitas Mataram, 2019)
Indonesia is geographically located in a strategic position between two continents, Asia and Australia, and two oceans,the Pacific and Indian Ocean. This factor allows many foreign ships to pass or anchor within Indonesian waters for trade and military purposes. Right of innocent passage applies to foreign ships and aircraft within the territorial sea. Foreign ships and aircraft are not allowed to engage in activities or crimes endangering the sovereignty of a nation or perform any violations towards the right of innocent passage. The legal purpose of this research is to know whether innocent passage endangers national sovereignty and learn how the law enforcements protect Indonesian territorial sea from foreign ships. The use of normative legal research reveals that the right of innocent passage in Indonesian waters is regulated in Law No. 17 of 1985 made as a ratification for the 1982 UNCLOS and the Institutions authorized to perform law enforcement in the sea through the employment of patrol task forces, namely Indonesian Naval force, Directorate of Water Police, Ministry of Maritime Affairs and Fisheries and Indonesian Maritime Security Board.